Getting away with murder: why do criminals succeed and detectives fail in neo-noir films? - Mancelos, João de (2016)
In classic film noir, villains and femmes fatales were nearly always punished for their crimes and transgressions. The Production Code demanded poetic justice, according to the ethical and moral principles of the forties and fifties. However, neo-noir films take a more realistic approach to life: on one side, the thug gets away with murder, proving that “good things happen to bad people”; on the other side, the tough police detective or private-eye, like Philip Marlowe or Sam Spade, was replaced by more humanized characters — morally ambiguous men or women who deal with existential issues and sometimes fail to catch the criminal. In this paper: a) I give evidence of how neo-noir film directors creatively use time and space to generate an atmosphere of insecurity and fear; b) I present and examine several examples of criminals who succeed and detectives who fail; c) I analyze the moral implications of these changes. In order to do so, I resort to several neo-noir films; to the work of specialists in film studies; and, of course, to my personal opinion.